2017
DOI: 10.2134/itsrj2016.05.0401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Herbicides and their Tank‐Mixes for Suppression of Bermudagrass in Zoysiagrass

Abstract: Zoysiagrass (Zoysia spp.) is a popular turfgrass species for use on lawns, sod farms, and golf courses in the transitional and southern climatic zones of the United States. One common problem in managing zoysiagrass is the contamination and subsequent removal of bermudagrass (Cynodon spp.). Various herbicides and herbicide tank‐mixes may be utilized for bermudagrass control in zoysiagrass. Research was conducted in Fayetteville, AR, and Auburn, AL, to evaluate aminocyclopyrachlor, fluazifop, fenoxaprop, triclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…A similar pattern was observed for the highest rate of fluazifop‐P‐butyl in summer and fall. Overall, Geo zoysiagrass maintained acceptable quality (i.e., ≥6) when triclopyr was included in the tank mixture, which agrees with previous studies with Cavalier, Meyer, and ‘Zorro’ zoysiagrass where triclopyr consistently maintained turf treated with fluazifop‐P‐butyl at acceptable levels (Patton et al, 2017b).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A similar pattern was observed for the highest rate of fluazifop‐P‐butyl in summer and fall. Overall, Geo zoysiagrass maintained acceptable quality (i.e., ≥6) when triclopyr was included in the tank mixture, which agrees with previous studies with Cavalier, Meyer, and ‘Zorro’ zoysiagrass where triclopyr consistently maintained turf treated with fluazifop‐P‐butyl at acceptable levels (Patton et al, 2017b).…”
Section: Resultssupporting
confidence: 89%
“…This is because greater control can be achieved after a single application by targeting the most susceptible growth stage of that weed population, such as targeting bermudagrass growth stage with 10-to 20-cm stolon for fluazifop-P-butyl application, as specified by the label. This reduced frequency of application could also translate to financial savings (Patton et al, 2017b). Previous studies have reported that triclopyr used alone on Emerald, Zorro, Cavalier, and Meyer zoysiagrass consistently led to <1% visual injury 6 WAT, which remains the case in our study for Zeon zoysiagrass but not for Empire or Geo zoysiagrass (Flessner et al, 2011a;Lewis et al, 2010;Patton et al, 2017b).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Fluazifop-P-butyl can be used for grass weed control in zoysiagrass establishment. However, the rate necessary to ensure weed control and zoysiagrass safety is largely dependent on the cultivar (Leon et al 2014;McElroy and Breeden 2006;Patton et al 2017b). Based on our results, fluazifop-P-butyl tolerance could be composed of multiple non-target site (NTS) mechanisms likely controlled by multiple genes that vary among different Zoysia genotypes, and as a result of this, conventional breeding approaches for creating more fluazifop-P-butyl-tolerant zoysiagrass lines will be challenging.…”
Section: Practical Implicationsmentioning
confidence: 88%